Microscopic study of the morphology and metabolic activity of Fusarium oxysporum f. sp. gladioli treated with Jatropha curcas oil and derivatives. Issue 1 (March 2016) - Cordova-Albores, L.C.; Zapotitla, E. Sandoval; Ríos, M.Y.; Barrera-Necha, L.L.; Hernández-López, M.; Bautista-Baños, S.
Abstract: The fungus Fusarium oxysporum f. sp. gladioli is one of the main pathogenic microorganisms of the ornamental genus Gladiolus . The attack of this microorganism includes corms and different plant phenological stages. In this study, different microscopic techniques and fluorochromes were used to evaluate the effect of J. curcas oil and acylglycerides, namely trilinolein, triolein, monomyristin and dimyristin, on the morphology, membrane integrity (%), viability (%) and germination (%) of F. oxsporum f sp. gladioli . Phase-contrast optical photomicrographs and scanning microscopy showed that J. curcas oil and the triglycerides triolein and trilinolein caused the formation of numerous vacuoles, alterations in the morphology of the outer covering of the mycelium and conidia, and inhibition of membrane activity in the fungus during 24 h of incubation. The fluorochromes used detected no permanent damage to the viability of the conidia. The high germination percentage of the conidia of Fusarium oxysporum f. sp. gladioli indicates that the damage caused by the application of the treatments was fungistatic rather than fungicidal and did not cause cell death.